The Decrease In The Intensity Of Menstrual Pain Before And After The Application Of Yoga In Class VIII Students At SMPN 1 Tanjung Bintang - Gusti Ayu Made Natasya Damayanti; Yuli Irnawati (Sean Institute, 2023)
Menstrual disorders that often occur in adolescents are menstrual pain or dysmenorrhea. Adolescents who experience menstrual pain will feel cramps in the lower abdomen and are usually accompanied by additional symptoms that interfere with daily activities. One effort that can be done to reduce it is to provide non-pharmacological therapy, namely yoga. The purpose of this study was to determine the difference in the decrease in the intensity of menstrual pain before and after the application of yoga. This research is an experimental study with a quasi-experimental design using the One Group Pretest Posttest design approach. The population in this study were all students of class VIII SMPN 1 Tanjung totaling 113 people with a total sample of 59 people. Data collection was carried out using questionnaires, observations, interviews, and literature. Data analysis using Paired T Test. The results showed the value of Sig. (2-tailed) of 0.000 so it can be concluded that there is a significant difference in the decrease in the intensity of menstrual pain before (pretest) and after (posttest) the application of yoga to class VIII students at SMPN 1 Tanjung Bintang. It is hoped that young women can take advantage of yoga therapy in dealing with menstrual pain and consult medical personnel if the pain becomes unbearable.